Towards developing a theoretical framework for measuring public sector managers' career success - Mohd Rasdi, Roziah; Ismail, Maimunah; Uli, Jegak; Mohd Noah, Sidek (Emerald, 2009)
Purpose – The purpose of this paper is to develop a theoretical framework for measuring public sector managers' career success.